Can Kindness Thwart Stigma Toward People With Special Educational Needs? Cross-Sectional and Longitudinal Evidence in the Philippine Context - Jesus Alfonso D. Datu; Randolph Chun Ho Chan Source Information
There is growing traction regarding the valuable effects of kindness on well-being and positive interpersonal functioning. However, existing literature has paid little attention to the association of kindness with discriminatory attitudes toward people with special educational needs (SEN). This research examined the link of kindness to stigma toward and acceptance of individuals with SEN among Filipino high school students using cross-sectional (Study 1) and longitudinal (Study) designs. In Study 1, the researchers used regression analyses to show that kindness negatively predicted stigma and positively predicted acceptance toward people with SEN, even after controlling for age and gender. In Study 2, the researchers adopted a cross-lagged panel structural equation modeling approach to demonstrate that Time 1 kindness positively predicted Time 2 acceptance even after controlling for auto-regressor effects. Time 1 kindness did not predict subsequent stigma. Findings allude to the significance of kindness in promoting positive attitude toward people with disabilities.